Price Elasticity of Nonresidential Demand for Energy in South Eastern Europe - Iimi, Atsushi (World Bank, Washington, DC, 2014)
Recent volatility in international energy prices has revealed South Eastern Europe as one of the most vulnerable regions to such external shocks. Under the current global economic downturn, in addition, the region s energy-intensive industries are faced with the challenge of the weakening demand for their outputs. This paper casts light on the relationship between the price and the demand for energy. Based on firm level data, it is shown that the price elasticity of industrial energy demand is about -0.4 on average. There are a number of data issues to interpret the results correctly. But Albania and Macedonia are systematically found to have a relatively elastic demand for energy on the order of -0.7 to -0.8. In these countries, therefore, price adjustments would be one of the effective policy options to balance demand with supply during the period of energy crisis. In other countries, the demand response would be much weaker; pricing cannot be the only solution. Other policy measures, such as facilitation of firm energy efficiency and improvements in the quality of infrastructure services, may be required.